The restaurant at the end of the universe - Adams, Douglas, 1952-2001 (Hitchhiker's Guide to the Galaxy, 2005)
Earthling Arthur Dent, Ford Perfect, and Zaphod Beeblebrox, the ex-president of the galaxy, are all aboard a space ship on a search for answers about life, the universe, and the perfect place to eat in space.